A Specific Kind of Representation: How Systematics May Ease Cognitive Overload - Özlem Cezikturk (Faculty of Teacher Training and Education, Universitas Muhammadiyah Surakarta, 2022)
Multiple representations are beneficial for meaningful understanding. However, three or more representations may add to the cognitive overload of students, if not in interactive diagrams and dynamic geometry. How a well-known representation consisting of more than 3 or more representational registers may overcome the problem of cognitive overload without being too complicated. In this study, an old but well-structured representation that was used even over 40 years was analyzed. The critical points of a function, asymptotes, x / y-intercepts, inflection points, and graphing can be identified easily. It is prepared in the form of a table and the factors of the first derivative of the function and the second derivative and their roots indicate the function’s increasing and decreasing intervals and its graph. This representation is very systematic and it acts like a method to draw the function’s graph with no-fault possible. Yet, besides being used for many years, is still used for courses like Calculus, etc. We argue that cognitive overload theory cannot alter this representation due to its systematic nature. In content analysis, some examples of this representation are shared via the reader, and some qualitative aspects about it are analyzed. Finally, its systematicity, well-structured nature, and nature in reducing extraneous cognitive load are emphasized. The important thing here is that it is very strategic not to lose some representations for the sake of new ones if their value is already known but not discussed too much.